Z Teorii Przestrzennych Rurociągów Samokompensacyjnych - Woźniak, C.; Łukowiak, M. (Engineering Transactions, 1965)
Ref. 1 represents a computation method of a ramified self-compensating pipeline. In this method transition equations are found for each branch, the cooperation between the branches being deter- mined by an iteration procedure. The transition equations (expressing the forces acting on the ends of the branches in terms) of [1] concern branches supported at extreme points only. These equations have been obtained taking into consideration both additional stiffening by means of intermediate supports and flexible compensating elements and various joints. Also the action of external concentrated and distributed loads is accounted for as well as the influence of prestress at any points of the network. In confrontation with other computation methods of ramified self-compensating pipelines the present method is characterized by a considerable generality of the considerations which are contained in a single computation scheme.